Share your rare with care: a patient corner for the European Reference Networks on Rare Disease. (30th September 2020) - Rubba, F; Montella, E; Carannante, I; Trummolo, M C; Simeone, A; Vozzella, E A; Magri, P; Iervolino, A; Colao, A; Triassi, M
Abstract: Background: The European Reference Network on Rare Disease (ERN) is focused on providing more equitable care across Europe and creates a network of both medical specialists and patient experts. One relevant objective of the activities planned into the ERNs is to address the economic dimensions of rare diseases in order to develop strategies to improve research and patients' access to orphan drugs (ODs) and highly specialized health technologies. The themes built in these preliminary years were directed toward guidelines and policies concerning reimbursement of ODs and direct provision by the healthcare system. Methods: to proceed further in humanization of care we establish involvement of patients' associations in decision making and implementation of clinical practice guidelines. We built in Federico II University Hospital where 12 ERN were aligned a front office corner shared between patients association and hospital direction in order to face the patient difficulties along the pathway. The corner is open three times a week on the morning, with a dedicated phone number. Results: Main issues regarded the understanding of the disease and the diagnosis (ie, lack of familiarity with the rare disease, disease heterogeneity, lack of established diagnostic criteria, misdiagnosis, ) the development of effective treatments and the need for efficacy along the path way of care (ie, geographical limitations, disease coding systems, ethical and privacy issues). Fewer concerns were about the equity of access and other social pressures. Conclusions In general, in ERN context, few people declared to work in human and social issues, including research on patient's quality of life, patient's awareness, or methods for social support. Our findings demonstrated that Patients were positively affected from the corner initiative: this may ameliorate the use of infrastructures offering services, also that rarely known as national and international biobanking platforms, registries and networks. Key messages: Humanization of care issues and strategies are nowadays mandatory in rare diseases. Patients are positively affected from shared initiatives.